Методика розрахунку параметрів промислового зразка струминно-щілинного гомогенізатора молока - Самойчук, Кирило Олегович; Ковальов, Олександр Олександрович; Фучаджи, Наталя Олександрівна; Samoichuk, Kyryl; Kovalov, Oleksandr; Fuchadzhy, Natalia (Запоріжжя : 2022, 2022)
UA: В статті було приведено вихідні дані для розрахунку основних конструктивних, гідравлічних, технологічних параметрів промислового зразку гомогенізатора в їх зв’язку з середнім діаметром жирових кульок після диспергування, потужністю приводів насосів та питомими енергетичними витратами процесу гомогенізації. Була розроблена методика розрахунку основних параметрів струминно- щілинного гомогенізатора молока в їх зв’язку з показниками якості та енерговитратами диспергування. Розраховані основні конструктивні параметри обладнання для продуктивності 1000, 2500, 5000 та 10000 кг/год. Отримані результати дозволять розробити промисловий зразок, скласти технічну документацію та передати її виробнику для впровадження в технологічні процеси переробки молока. EN: Increasing the energy efficiency of the process of dispersing dairy products is an urgent task, since more than 8 kWh/t of electrical energy is spent on the processing of one ton of product. The results of prospective studies allow us to state that a significant reduction in energy costs for homogenization can be achieved through the development and implementation of designs in production, the principle of operation of which is based on creating the maximum difference between the speeds of the dispersed (skimmed milk) and dispersed (cream) phases of the product. For the implementation of the developed structures and the practical implementation of the obtained results in the conditions of real production, it is necessary to develop a methodology for calculating the industrial model of the jet-slit milk homogenizer. To achieve this goal, the article provided initial data for calculating the main structural, hydraulic, and technological parameters of an industrial model of a jetslit homogenizer in relation to the average diameter of fat balls after dispersion, the power of pump drives, and the specific energy consumption of the homogenization process. Among the parameters determined by the sequence of calculation should be mentioned the productivity of skimmed milk and cream, the speed of skim milk, the diameter of the chamber at the point of the largest narrowing, the speed of the cream, the excess pressures of the pumps supplying the dispersion and dispersed phase, the power of the pumps and the specific energy consumption of the process. The article provides data on selected pumps, electric motors and gears used to supply skimmed milk and cream. The main design parameters of the equipment are calculated for the productivity of 1000, 2500, 5000 and 10000 kg/h. The obtained results will make it possible to develop an industrial model, draw up technical documentation and hand it over to the manufacturer for implementation in the technological processes of milk processing and to calculate, based on the obtained data, the economic efficiency indicators of the introduction of an industrial model of a jet-slit milk homogenizer with separate cream supply. Keywords: productivity, industrial model,
Method of calculating the parameters of the industrial sample of the flow-slot milk homogenizer
Самойчук К. О., Ковальов О. О., Фучаджи Н. О. Методика розрахунку параметрів промислового зразка струминно-щілинного гомогенізатора молока. Науковий вісник Таврійського державного агротехнологічного університету : електронне наукове фахове видання. 2022. Вип. 12. том 3. C. 54-63.
Keywords: продуктивність; промисловий зразок; струминно-щілинний гомогенізатор; енергоефективність; гомогенізація; розрахунок; productivity; industrial model; jet-slit homogenizer; energy efficiency; homogenization; calculation